Allelopathic potential of aqueous extracts of Bidens pilosa L., Cyperus rotundus L., and Euphorbia heterophylla L. - Gusman, Grasielle Soares (2011)
This study aimed to identify possible allelopathic effects of aqueous extracts of Cyperus rotundus L., Bidens pilosa L. and Euphorbia heterophylla L. on the germination and initial development of four leafy vegetables. Five concentrations of the aqueous extracts were tested (10, 30, 50, 70 and 100 %) and compared to a control (0.0%), with ten seeds of the cultivated species distributed in each of fi ve replicates. The aqueous extracts of three invasive species showed allelopathic potential on seed germination, on initial root and shoot growth, and on the germination speed rate of seeds of all the leafy vegetables tested. The initial growth was more affected when compared to the germination process, and the structure that was more affected when exposed to the aqueous extracts was the seedling roots, which resulted in thicker and atrophied roots with a higher number of absorbing hairs. Of the invasive species tested, B. pilosa and E. heterophylla were the ones considered potentially allelopathic.